TAX PLANNING AND ITS LEGALITY - Saswati, Riniadi; Syafi'i, M. (jfpublisher, 2022)
Paying taxes is the duty of every citizen, within the framework of participation in nation to build the obedience in paying tax. However, on the other hand, as citizens (taxpayers) will miss some of the